Effect of spring constant and thrust constant to displacement characteristics of slot type moving magnet of LOA - Misron, Norhisam; Abdul Shukor , Fairul Azhar; Raja Othman, Raja Nor Firdaus Kashfi; Hazim, Hisham; Nirei, Masami; Wakiwaka, Hiroyuki; Jelani, Abdul Razak (2009)
This paper discuss the effect of spring constant and thrust constant to the displacement characteristics of LOA. A mathematical expression to represent the LOA has been derived to observe the effect of spring constant and thrust constant to the displacement of LOA. It is shown that the thrust constant is only influence to the value of peak displacement. However, the spring constant will affect the value of frequency resonance. Furthermore, at optimum value of spring constant will give maximum value of displacement. The LOA is aimed to have a peak displacement of 5 mm at operation frequency of 60 Hz. Consequently, the suitable value of spring constant has been choose and the measurement result is use to verify the calculation result. It is shown a good agreement between these results.